GUIDED EXPERIMENTS BOOK BERBASIS SETS (SCIENCE ENVIRONMENT, TECHNOLOGY, AND SOCIETY) UNTUK MEMBERDAYAKAN SCIENCE PROCESS SKILL SISWA SEKOLAH DASAR - Tri Prasasti, Pinkan Amita; Listiyani, Ivayuni (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2018)
The Guided Experiment Book based on SETS is a guidebook for students in carrying out scientific work. The SETS-based Guided Experiment Book helps students to develop their skills and get to know the scientific process to get concepts. The aim of this research is to empower Science Process Skill through the SETS based Guided Experiment Book. This study involved 50 grade V students divided into 2 groups including 25 students in the intervention group and 25 students in the control group. Activities are carried out for a period of 3 months outside of school activities. Empowerment of Science process skill seen from the increase in results before and after the implementation of the Guided Experiment Book based on SETS. Guided Experiment Book based on SETS helps students to empower the Science Process Skill through the stages of invitations, exploration, problem solving, application concepts and conclusions. These stages are activities that familiarize students to learn concepts through processes and apply technology that is environmentally sound. Based on the results of research and testing hypotheses it can be concluded that the SETS-based Guided Experiment Book can empower scientific literacy of elementary school students.